Evaluation of growth and yield performance of important three tomato varieties released by Bangladesh Agricultural Research Institute - Haq, Mohammad Tojammel; Ahmed, Md Shamim (Research in Agriculture Livestock and Fisheries, 2022)
An experiment was conducted at Bangabandhu Academy for Poverty Alleviation and Rural Development (BAPARD) Agricultural Farm, Kotalipara, Gopalganj during December, 2019 to May, 2020 to find out the vegetative growth and yield performance of three BARI tomato varieties viz. BARI Tomato-11, BARI Tomato-14 and BARI Tomato-15. The plant height of BARI Tomato- 11,BARI Tomato-14, BARI Tomato-15 were 8.21cm, 7.17cm, 8.82cm, 8.73cm, 7.75cm, 9.37cm, 15.40cm, 13.24cm, 14.40cm respectively at 0 DAT, 10 DAT, 20 DAT with significantly increase 20 DAT except 0 DAT and 10 DAT. First flowering of BARI Tomato-11, BARI Tomato-14 and BARI Tomato-15 was 39 DAT, 40 DAT and 41 DAT which was statistically identical. Number of fruits per plant and weight of individual fruit of BARI Tomato-11, BARI Tomato-14, BARI Tomato-15 were 142.96, 34.92, 30.95 and 10.85gm, 78.5gm, 59.9gm respectively. In case of number of fruits per plant, BARI Tomato-11 showed the maximum but weight of individual fruit was very low because of size and shape was very small. Fruit yield of BARI Tomato-11, BARI Tomato-14 and BARI Tomato-15 were51.67 t/ha, 91.33 t/ha and 61.67 t/ha, respectively. The present study concluded that BARI Tomato-14 is more suitable for this area. Res. Agric., Livest. Fish.9(1): 37-42, April 2022